World? Which World? On Some Pitfalls of a Concept - Klepec, Peter (Filozofski vestnik, 2022)
“The world” as a concept necessarily involves many difficulties and contradictions. The text presents some of them in a rather circular way, underlining the fact that we are always confronted with the dilemma of what to do with the world, or rather, what, which, and whose world we are dealing with. Beginning with some arguments about the claim that “the world is (out there),” and then moving on to certain dilemmas related to some views on the two-world theory, one inevitably comes across Marx’s thesis that the ultimate goal in relation to the world should be to “change it”. The text also presents some contemporary views thereon of Badiou, Nancy, and Ruda. Taking into account all these arguments and adding insights from Freud, Husserl, Heidegger, and Adorno as to the world and one’s worldview, we can only agree with Badiou’s statement about the only true goal of philosophy: “Philosophy has no other legitimate aim except to help find the new names that will bring into existence the unknown world that is only waiting for us because we are waiting for it.”